Usulan Perbaikan Tata Letak Gudang Pendingin yang Memaksimalkan Daya Tampung dan Meminimumkan RataRata Jarak Perpindahan (Studi Kasus PT. XYZ) - Hidayat, Trifenaus Prabu; Yanuwar, Aliffian; Silalahi, Agustinus (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
PT. XYZ’s Cold Storage that is located in the Pelabuhan Perikanan Samudera Nizam Zachman Jakarta currently does not implement a storage layout system, the are randomly placed, even an empty area near the door is not utilized to put the commodity to be stored. Causing the forklift mileage to grow larger. In addition, the demand for cold storage is increasing from year to year so that cold storage should be increased current capacity, cold storage is currently able to accommodate 575 pallets. The increase in cold storage capacity is done by combining the storage flow, pallet laying position, as well as the layout method of class based storage, dedicated storage, and random storage. The combination of these three factors resulted in 18 possible proposals for the improvement of the cold storage layout. From the 18th combinations likely to be taken one combination of layouts by considering three criteria i.e. maximum capacity, minimum distance, and maximum revenue gained from maximum capacity. Proposal layout with a combination of pallet widened position, simple straight groove, with dedicated storage method to be the best proposal with a maximum capacity of 750 pallets, the minimum distance of 5728.82 m, and the company can earn a maximum income of Rp 297 million per month with the capacity.